Remittances in Pakistan Why have they gone up, and why Aren't they coming down? - Sun, Yan (International Monetary Fund, 2011)
The flow of workers'' remittances to Pakistan has more than quadrupled in the last eight years and it shows no sign of slowing down, despite the economic downturn in the Gulf Cooperation Council (GCC) and other important host countries for Pakistani workers. This paper analyses the forces that have driven remittance flows to Pakistan in recent years. The main conclusions are: (i) the growth in the inflow of workers'' remittances to Pakistan is in large part due to an increase in worker migration; (ii) higher skill levels of migrating workers have helped to boost remittances; (iii) other imporant determinants of remittances to Pakistan are agriculture output and the relative yield on investments in the host and home countries